Criminal Liability Of Medical Personnel In Law Number 17 Of 2023 Concerning Health - Abang Anton; Beny Satria; Yasmirah Mandasari Saragih (International Journal of Law, Crime and Justice, 2024)
Healthcare services, conflicts often arise between doctors and patients, involving allegations of medical criminal actions. Health laws are designed to provide greater certainty in the administration of healthcare services and to offer protection for both the public and healthcare resources. This research adopts a normative juridical approach, employing qualitative descriptive methodology. Medical professionals may face criminal charges for engaging in illegal abortions, performing reconstructive and aesthetic plastic surgery with the intent to alter someone's identity, refusing healthcare services in emergency situations, committing negligence, and practicing Without a License (STR) and/or Practice Permit (SIP). Medical professionals are obliged to adhere to professional standards, service standards, and operational procedure standards, while upholding the values of professional ethics and exerting their best efforts (Inspanning Verbintenis). Dispute resolution should initially take place through restorative justice mechanisms, utilizing alternative methods outside the court.